Pengaruh Penerapan Fungsi – Fungsi Manajeman terhadap Kreativitas Kerja Pegawai : pada Kantor Dinas Pemuda Olahraga dan Pariwisata Kabupaten Wajo - Burhanuddin Burhanuddin; Muktamir Usman; Supris Musiafir; Ekayani Burhanuddin (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
Employees at the Wajo Regency Youth, Sports, and Tourism Office are part of the public bureaucracy at the district/city level who have important responsibilities in carrying out service functions to the public. Based on initial observations, it appears that the implementation of management functions and employee work creativity are still not optimal. This is primarily related to the implementation of management functions in creating a dynamic work atmosphere and in terms of making the best use of time. Effective management is essential to ensure that public organizations can achieve their goals efficiently and innovatively. This study aims to determine the effect of the implementation of management functions on employee work creativity at the Wajo Regency Youth, Sports, and Tourism Office. The study population was all employees at the office, using a survey method and an associative quantitative approach. This technique was chosen to obtain an objective picture of the relationship between management variables and work creativity. The results show that the management functions variable, based on respondents' responses, is in the very good category. Meanwhile, the employee work creativity variable is in the good category. The findings indicate that the proper application of management functions can significantly foster employee creativity. Based on statistical testing, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Thus, it can be concluded that the implementation of management functions has a positive and significant impact on employee creativity at the Wajo Regency Youth, Sports, and Tourism Office. This research provides practical implications: public organizations need to strengthen the implementation of management functions, such as planning, organizing, directing, and controlling, to continuously improve employee creativity. This research highlights the importance of integrating managerial functions with innovative practices in the public sector.